2013
DOI: 10.1128/jcm.01787-13
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Colistin Resistance in Clinical Strains of Acinetobacter baumannii by Use of the Micromax Assay

Abstract: Colistin is an old antibiotic which has been used as a therapeutic option for carbapenem-and multidrug-resistant Gram-negative bacteria, like Acinetobacter baumannii. This pathogen produces life-threatening infections, mainly in patients admitted to intensive care units. Rapid detection of resistance to colistin may improve patient outcomes and prevent the spread of resistance. For this purpose, Micromax technology was evaluated in four isogenic A. baumannii strains with known mechanisms of resistance to colis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Micromax assay (Halotech DNA SL, Madrid, Spain) is based on the detection of DNA fragmentation and cell wall damage in the presence of colistin [86]. Bacteria are incubated for 60 min with 0.5 µ g/ml of colistin, trapped in a microgel, and then incubated with a lysis solution to remove weakened cell walls.…”
Section: Phenotypic Detection Methodsmentioning
confidence: 99%
“…The Micromax assay (Halotech DNA SL, Madrid, Spain) is based on the detection of DNA fragmentation and cell wall damage in the presence of colistin [86]. Bacteria are incubated for 60 min with 0.5 µ g/ml of colistin, trapped in a microgel, and then incubated with a lysis solution to remove weakened cell walls.…”
Section: Phenotypic Detection Methodsmentioning
confidence: 99%
“…The Micromax assay is based on the detection of released nucleotides, indicating cell wall damage, in the presence of colistin (104). After incubation with 0.5 g/ml of colistin, strains are considered resistant to colistin if Յ11% of bacteria present cell wall damage.…”
Section: Qualitative Detection Techniquesmentioning
confidence: 99%
“…This situation demonstrates the need for the development of accurate and reliable methods for detecting colistin resistance. Recently, several methods for the identification of colistin resistance were reported, including various routine colistin MIC testing methods, such as BMD, BMD-P80, AD, Etest, MTS, and Vitek2 ( Dafopoulou et al, 2015 ; Humphries, 2015 ); capillary electrophoresis method according to characteristic surface properties of bacteria ( Sautrey et al, 2015 ); and the micromax assay based on evaluation of the efficacy of antibiotics that affect cell wall integrity ( Tamayo et al, 2013 ). Because a recent report showed that the mcr-1 gene, involved in the modification of lipid A, is a major contributor to colistin resistance in Gram-negative bacteria ( Liu et al, 2016 ), detection of this gene may be important in the detection of colistin resistance.…”
Section: The Epidemiology Genetic Context Treatment Options and Dementioning
confidence: 99%